PENGARUH EDUKASI MANAJEMEN STRES TERHADAP MEKANISME KOPING MASYARAKAT DALAM MENGHADAPI PANDEMI COVID -19 DI DUSUN V PASAR IV SUKA RENDE KECAMATAN KUTALIMBARU - Dwi Wahyuni Putri; Hendry Kiswanto Mendrofa (Indonesian Trust Nursing Journal, 2023)
The Corona Virus Disease 2019 (COVID-19) pandemic is increasingly widespread and spreading to almost all over the world including in Indonesia, the number of cases is getting higher and increasing every day. This case raises its own concerns for the community. The general response of someone who is exposed, either directly or indirectly, is fear of getting sick and dying, fear of being infected, not wanting to come to a health facility, causing stress to the community. Purpose: To identify the effect of stress management education on community coping mechanisms in dealing with the COVID-19 pandemic. The objective of this study is identify the effect of stress management education on community coping mechanisms in dealing with the COVID-19 pandemic. This Research using Quasi experimental with one group pre-post test. The population in this study were the people in Hamlet V Pasar IV Suka Rende, Kutalimbaru District, consisting of 127 families. Sampling by purposive sampling technique with a total sample of 32 respondents. The instrument used is a questionnaire with an independent hypothesis test wilcoxon. The result of this study, before the stress management education was carried out, the majority of adaptive community coping mechanisms were 25 people (78.1%), after the stress management education was carried out, the majority of adaptive community coping mechanisms were carried out, as many as 32 people (100%). There is an effect of stress management education on community coping mechanisms in dealing with the COVID-19 pandemic in Hamlet V Pasar IV Suka Rende, Kutalimbaru District, with a p value of 0.000. It is suggested that people to always do stress management to prevent prolonged stress and increase their knowledge about stress management. Abstrak Pandemi Corona Virus Disease 2019 (COVID-19) semakin meluas dan menyebar hampir di seluruh dunia termasuk di Indonesia, jumlah kasus setiap harinya semakin tinggi dan bertambah dengan cepat. Kasus ini menimbulkan kekhawatiran tersendiri bagi masyarakat. Respons umum dari seseorang yang terpapar baik secara langsung atau tidak yaitu ketakutan sakit dan meninggal dunia, takut tertular, tidak ingin datang ke fasilitas kesehatan sehingga menimbulkan stress kepada masyarakat. Penelitian ini bertujuan untuk mengidentifikasi pengaruh edukasi manajemen stres terhadap mekanisme koping masyarakat dalam mengahadapi pandemi COVID-19. Penelitian menggunakan Quasi experimental dengan one group pre-post test. Populasi dalam penelitian ini adalah masyarakat di Dusun V Pasar IV Suka Rende Kecamatan Kutalimbaru sebanyak 127 keluarga. Pengambilan sampel dengan teknik purposive sampling dengan jumlah sampel 32 responden. Instrumen yang digunakan adalah lembaran kuesioner dengan uji hipotesis wilcoxon. Hasdil penelitian, sebelum dilakukan edukasi manajemen stress mayoritas mekanisme koping masyarakat adaptif sebanyak 25 orang (78,1%), sesudah dilakukan edukasi manajemen stress mekanisme koping masyarakat mayoritas adaptif sebanyak 32 orang (100%). Terdapat Pengaruh edukasi manajemen stress terhadap mekanisme koping masyarakat dalam menghadapi pandemi COVID-19 di Dusun V Pasar IV Suka Rende Kecamatan Kutalimbaru dengan nilai p value 0,000. Direkomendasikan agar masyarakat untuk senantiasa selalu melakukan manajemen stres untuk mencegah terjadinya stres yang berkepanjangan dan meningkatkan pengetahuannya tentang manajemen stres.